2014
DOI: 10.4300/jgme-d-13-00412.1
|View full text |Cite
|
Sign up to set email alerts
|

Brand Name Statin Prescribing in a Resident Ambulatory Practice: Implications for Teaching Cost-Conscious Medicine

Abstract: Background Several national initiatives aim to teach high-value care to residents. While there is a growing body of literature on cost impact of physicians' therapeutic decisions, few studies have assessed factors that influence residents' prescribing practices. Objective We studied factors associated with intensive health care utilization among internal medicine residents, using brand name statin prescribing as a proxy for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…A prior study found that the medical school care intensity environment influenced resident prescribing of generic medications. 12 Furthermore, although we aimed to study an aspect of physician behavior related to costeffective care, our findings may represent a more general relationship between attending and resident practice styles across other practice behaviors not related to cost. Availability of databases containing residency program scheduling, faculty, and resident characteristics and practice patterns would enable researchers to identify specific factors that influence these and other practice behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prior study found that the medical school care intensity environment influenced resident prescribing of generic medications. 12 Furthermore, although we aimed to study an aspect of physician behavior related to costeffective care, our findings may represent a more general relationship between attending and resident practice styles across other practice behaviors not related to cost. Availability of databases containing residency program scheduling, faculty, and resident characteristics and practice patterns would enable researchers to identify specific factors that influence these and other practice behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the ambulatory setting, a study of resident prescribing practices found considerable variation in generic vs. brand-name statin prescribing by residents after controlling for the effect of the supervising attending. 12 After completing training, less experienced physicians had higher overall cost profiles than more experienced physicians. 13 Although these findings suggest that residents do not perfectly mirror their attending physicians' practice patterns, the relationship between attending physicians and the practice of residents that they supervise has not been studied directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the residents at all levels are likely to prescribe the expensive statin medications even when the generic versions are visible. 1 There is also some evidence that junior physicians have higher cost profiles than physicians with greater experience. 2 In 2008, Kesselheim et al 3 showed that despite paucity of evidence that brand drugs are superior to the generic formulations, editorialists frequently raise concerns regarding the efficacy of generic drugs and advocate against the interchangeability.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Graduate Medical Education, Ryskina et al 14 begin to explore the connections among various training factors and the propensity for brand name statin prescribing. They conclude that residents at a single urban academic residency clinic prescribe brand name statins at highly variable rates: when residents were categorized into quintiles by rate of brand name statin prescribing, the bottom quintile prescribed brand name statins in 1.7% of encounters and the top quintile in 98.2% of encounters.…”
mentioning
confidence: 99%